2011
DOI: 10.1016/j.molimm.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Increased GABAA channel subunits expression in CD8+ but not in CD4+ T cells in BB rats developing diabetes compared to their congenic littermates

Abstract: "Increased GABA(A) channel subunits expression in CD8(+) but not in CD4(+) T cells in BB rats developing diabetes compared to their congenic littermates"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 27 publications
(40 reference statements)
2
52
0
1
Order By: Relevance
“…Specifically, targeting a4b2/3d receptors for treating various CNS (see Introduction and references therein), as well as non-CNS (e.g. type 1 diabetes; see (Mendu et al, 2011) disorders is gaining momentum. It is now evident that d-GABAA receptors exhibit a restricted neuronal distribution, are primarily found peri-or extrasynaptically, exhibit distinct biophysical properties compared with synaptic GABAA receptors and are not affected by clinically used benzodiazepines.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, targeting a4b2/3d receptors for treating various CNS (see Introduction and references therein), as well as non-CNS (e.g. type 1 diabetes; see (Mendu et al, 2011) disorders is gaining momentum. It is now evident that d-GABAA receptors exhibit a restricted neuronal distribution, are primarily found peri-or extrasynaptically, exhibit distinct biophysical properties compared with synaptic GABAA receptors and are not affected by clinically used benzodiazepines.…”
Section: Tablementioning
confidence: 99%
“…Clearly, this does not preclude DS2 being administered directly into brain ventricles or discrete brain regions in future studies. However, potentially of more interest, given the excellent plasma exposure of DS2 in mice and rats, is to consider assessing DS2 in animal models of disorders with a peripheral/non-CNS basis (Mendu et al, 2011).…”
Section: In Vivo Propertiesmentioning
confidence: 99%
“…Здесь и в таблице 2 результаты представлены в виде средней ± ошибка средней; * -р<0,05 по отношению к контролю; # -р<0,05 по отношению к группе с алкогольной интоксикацией; & -р<0,05 по отношению к инфликсимабу в дозе 1 мг/кг. Т-лимфоцитов [17,18] (табл. 2).…”
Section: * -адресат для перепискиunclassified
“…So far there are relatively few studies that have looked at the GABA system in immune cells ( (Bjurstom et al 2008) and in CD4 + and CD8 + T cells from rats a1, a2, a3, a4, a6, b3, g1, d, r1 and r2 were identified out of the 19 subunits examined (Mendu et al 2011). As only in two of the studies was the expression of all the different subunits was examined, it is possible that more subunits types can be detected in the T cells from the mouse models or alternatively, the GABA-A subunits expression may be regulated according to e.g.…”
Section: 2mentioning
confidence: 99%
“…Bergeret et al (1998) reported that GABA modulates cytotoxicity of immunocompetent cells expressing GABA-A ion channel subunits. GABA opens the plasma membrane GABA-A ion channels in the immune cell generating a chloride current across the membrane (Bjurstom et al 2008;Bhat et al 2010;Mendu et al 2011). GABA application can result in decreased cytokine secretion and proliferation of T cells (Tian et al 2004;Bjurstom et al 2008;Mendu et al 2011) or have no effects on these properties of the cells (Bhat and Steinman 2009).…”
Section: Effects Of Gaba On Immune Cellsmentioning
confidence: 99%